SMART PAWON: SMART PANTI ASUHAN WEB ON NETWORK SEBAGAI TEKNOLOGI TEPAT GUNA UNTUK PENGEMBANGAN PANTI ASUHAN DI KOTA MALANG - E., Elwin; S., Sutrisno; Prasetiyo, Azis Rizal (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Orphanages as institutions which accommodate, nurture, and educate orphans and underprivileged, majority are unable to survive long due to lack of public support. The lack of such assistance due to lack of publication of the existence of an orphanage to the general public and donors. To solve this problem, we did community service to orphanages in order to publicize its existence to the general public and donors with the title: Smart Pawon: âSmart Orphanage Web On Network as the Applied Technology for Developing Orphanage in Malang". The objective of this community service is to publicize the existence of the orphanage to the public and donors that will be easier for them to locate and provide assistance to orphanages. With the help of the community and donors, the orphanage is expected to be able to survive and rapidly evolving. This community service has been carried out for 4 months from preparation, data collection, purchase a domain and website creation, website management training and publications websites existence. Equipment used include computers, the Internet, and the supporting equipment such as tables, and electrical current. Community service that has been done has realized the target outcome is the creation of a website holding orphanages www.pawon.net site map with the address, and the creation of a website that is a partner orphanage orphanage website Nurul Abyadh www.nurulabyadh.com, Sunan Ampel orphanage website www.pa-sunanampel.com, website â Taqwa-Alqolbi orphanage www.taqwa-alqolbi.com. As a result, the community service has been declared a success because there has been a significant increase in the number of donations to the orphanage partners.